2009
DOI: 10.1029/2008jc005182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high‐resolution sea ice models on the basis of statistical and scaling properties of Arctic sea ice drift and deformation

Abstract: [1] Sea ice drift and deformation from models are evaluated on the basis of statistical and scaling properties. These properties are derived from two observation data sets: the RADARSAT Geophysical Processor System (RGPS) and buoy trajectories from the International Arctic Buoy Program (IABP). Two simulations obtained with the Louvain-la-Neuve Ice Model (LIM) coupled to a high-resolution ocean model and a simulation obtained with the Los Alamos Sea Ice Model (CICE) were analyzed. Model ice drift compares well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 47 publications
7
125
3
Order By: Relevance
“…The comparison of the ice drift from TOPAZ with that from IABP buoys and the Tara expedition (not shown) 650 P. Sakov et al: TOPAZ4 system reveals that the model ice drift is generally slightly too fast, by 3 km day −1 for slow drift as much as for fast drift, which is a known deficiency of the EVP type of model: Girard et al (2009) reported an even larger bias of 6 to 7 km day −1 . The too fast ice drift is advecting too much ice into the Beaufort Sea and is consistent with the ice pack being spread out, as mentioned above.…”
Section: Evaluation Of Ice Fieldsmentioning
confidence: 99%
“…The comparison of the ice drift from TOPAZ with that from IABP buoys and the Tara expedition (not shown) 650 P. Sakov et al: TOPAZ4 system reveals that the model ice drift is generally slightly too fast, by 3 km day −1 for slow drift as much as for fast drift, which is a known deficiency of the EVP type of model: Girard et al (2009) reported an even larger bias of 6 to 7 km day −1 . The too fast ice drift is advecting too much ice into the Beaufort Sea and is consistent with the ice pack being spread out, as mentioned above.…”
Section: Evaluation Of Ice Fieldsmentioning
confidence: 99%
“…One of the reasons to redesign or replace the VP and EVP rheologies is that classical models give a poor representation of ice drift and deformation statistics and scaling, compared with satellite observations (Girard et al, 2009). Girard et al (2011) introduced the elasto-brittle rheology and showed that this has the potential to accurately reproduce the aforementioned statistics and scaling.…”
Section: P Rampal Et Al: Nextsim: a New Lagrangian Sea Ice Modelmentioning
confidence: 99%
“…A local structure tensor in a sea ice model as a measure of the sub-continuum anisotropy (such as leads) of the sea ice cover results in substantially changed sea ice thickness and drift in comparison to a reference run [10]. Girard et al [11] conclude that the poor representation of observed sea ice deformation patterns that represent lead structures in two high-resolution sea ice models could mainly be addressed to the used mechanical framework. The build-up of leads and the consequent anisotropy of the sea ice deformation can be captured within an elasto-brittle or an elastic-decohesive framework [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%